2003
DOI: 10.1186/1471-2199-4-2
|View full text |Cite
|
Sign up to set email alerts
|

Viable nonsense mutants for the essential gene SUP45 of Saccharomyces cerevisiae

Abstract: BackgroundTermination of protein synthesis in eukaryotes involves at least two polypeptide release factors (eRFs) – eRF1 and eRF3. The highly conserved translation termination factor eRF1 in Saccharomyces cerevisiae is encoded by the essential gene SUP45.ResultsWe have isolated five sup45-n (n from nonsense) mutations that cause nonsense substitutions in the following amino acid positions of eRF1: Y53 → UAA, E266 → UAA, L283 → UAA, L317 → UGA, E385 → UAA. We found that full-length eRF1 protein is present in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 63 publications
0
43
0
Order By: Relevance
“…In this study, the properties of one such feedback example were examined because it represents an unusual example of negative feedback operating at the level of translation. Nonsense mutations in the essential SUP45 gene encoding the release factor eRF1 are not, as would be expected, lethal, but instead form a viable eRF1 expression system in which levels of eRF1 are maintained by significant levels of stop codon readthrough (Stansfield et al 1996;Moskalenko et al 2003). However, the properties of the eRF1 feedback loop and its response to perturbation have not previously been investigated.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this study, the properties of one such feedback example were examined because it represents an unusual example of negative feedback operating at the level of translation. Nonsense mutations in the essential SUP45 gene encoding the release factor eRF1 are not, as would be expected, lethal, but instead form a viable eRF1 expression system in which levels of eRF1 are maintained by significant levels of stop codon readthrough (Stansfield et al 1996;Moskalenko et al 2003). However, the properties of the eRF1 feedback loop and its response to perturbation have not previously been investigated.…”
Section: Discussionmentioning
confidence: 98%
“…The mutant SUP45 phenotypes exhibit increased nonsense suppression, which promote tRNA-mediated readthrough of the early stop codon and hence production of some reduced level of full-length release factor (Stansfield et al 1996). eRF1 nonsense mutations of this type have been isolated in the presence of specific mutant suppressor tRNAs that help support readthrough of the premature stop codon (Stansfield et al 1996), but intriguingly, also in wild-type tRNA backgrounds (Moskalenko et al 2003). The level of readthrough of the premature eRF1 nonsense codons is regulated by a complex interaction between the suppressor tRNA efficiency (Stansfield et al 1996;de Silva et al 2010), the eRF1 protein stability and activity, and the modulatory effect of the nonsense-mediated mRNA decay system that acts to destabilize mRNAs carrying early stop codons (Chabelskaya et al 2007;Kiktev et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The S. cerevisiae strains used in this study were as follows: 1B-D1606 (MAT ade1-14 his7-1 leu2-3,112 ura3-52 trp1-289 lys9-A21 [psi ¡ ]) (Moskalenko et al 2003 (Derkatch et al 1996;Newnam et al 1999 (Moskalenko et al 2003) was used. Previously characterized nonsense mutant alleles of sup45 (sup45-n) used in this study were: sup45-101 (266E !…”
Section: Strainsmentioning
confidence: 99%
“…However, viable nonsense mutant alleles have been obtained for both SUP45 and SUP35 genes (StansWeld et al 1996;Zhou et al 1999;Cosson et al 2002;Bradley et al 2003;Moskalenko et al 2003;Chabelskaya et al 2004;Valouev et al 2004). Previously, we have shown that some sup45 nonsense mutations (sup45-n) do not completely abolish accumulation of fullsize eRF1.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation